PENGGUNAAN GAMIFIED LEARNING MELALUI PLATFORM GENIALLY PADA PEMBELAJARAN SOSIOLOGI DI KELAS XI SMAIT AL-MUMTAZ PONTIANAK - Putri, Marbela Vaderofa; Ramadhan, Iwan (Jurnal Pendidikan Edukasi Kusuma Bangsa, 2025)
This study aims to analyze the use of gamified learning through Genially in sociology instruction for eleventh-grade students at SMAIT AL MUMTAZ Pontianak. The research focuses on the planning process, implementation, and learning effectiveness for students using gamified learning via Genially in sociology classes. This study employs a qualitative research method. Data were collected through observation, interviews, and documentation, involving the sociology teacher and four eleventh-grade students as research subjects. The findings indicate that the use of gamified learning through Genially was systematically planned, taking into account the readiness of both teachers and students. The implementation of gamification via Genially was able to transform passive lessons into active ones, thereby creating a communicative learning process and generating positive responses from students. The use of gamified learning through Genially in sociology instruction also proved to be an effective method for increasing student engagement and motivation. In conclusion, the use of gamified learning through Genially by the sociology teacher in the eleventh grade at SMAIT AL MUMTAZ Pontianak not only made learning more active and enjoyable but also served as an effective approach to fostering responsive and communicative learning among students during sociology lessons.